Intertrochanteric fracture neck treatment with percutaneous dynamic hip screw fixation technique: understanding outcomes in elderly patients - Muhammad Ikram; Nadia Gul; Sajid Ejaz Rao; Sadia Ijaz; Munawer Latif Memon; Sohail Muzammil (Journal of University Medical & Dental College, 2024)
Background and Objective: Femur fractures result in a high rate of mortality and morbidity. Objective was to compare effectiveness of percutaneous dynamic hip screw fixation technique (PC-DHS) and conventional open dynamic hip screw (DHS) in terms of mean operative time, wound size, pain scores, intraoperative blood loss, screening time, hospital stay at 2 weeks, mean full weight bearing mobilization at 6 weeks, mean hip Harris scores at 6 weeks and 3 months and mean radiological healing at 3 months in older patients having an intertrochanteric fracture of femur neck at tertiary care hospital. Methodology: The study design was a prospective observation study at the Department of Orthopedics, POF hospital. The study duration was 2 years (2018-2020). The sample size was 130 with 1:1 randomization in each group. Patients were selected through nonprobability sampling (lottery method) and divided into two groups; Group A underwent PC-DHS and Group B underwent conventional DHS procedure. Data was analyzed using SPSS version 24. Results: A total of 130 patients were studied. Patients who underwent PC-DHS showed significantly low operative time (p<0.00), wound size (p<0.00), intraoperative blood loss (p<0.00), pain scores (p<0.00), hospital stay length (p<0.00) at 2 weeks as compared to conventional DHS. PC-DHS patients showed high Hip scores (p<0.00) at 3 months and at 6 months (p<0.00). The frequency of chronic hip pain, non-union, implant failure, avascular necrosis, chronic osteomyelitis, and deep venous thrombosis was high in conventional open DHS. Conclusion: We found PC-DHS as a more effective and safe technique for intertrochanteric fracture fixation resulting in significant improvement in surgical outcomes at 2 weeks, 6 weeks, 3 months, and 6 months.